Factor structure of time-sharing performance at a higher level of practice - Jerneić, Željko; Šverko, Branimir; Maslić-Seršić, Darja (1994)
A number of studies have sought support for the notion of time-sharing ability by analyzing the factor structure of dual task performance. In such studies the subjects perform several tasks both singly and concurrently, and their performance is then factor-analyzed to determine whether a time-sharing factor under lying concurrent-task performance could be identified. No study has identified the general time-sharing factor. Only group factors, limited to some combinations of time-shared tasks, have been found instead. However, only the performance at a low level of practice has been measured, and it is possible that the factor structure is different at a higher level of practice. In this study, therefore, we have attempted an analysis at higher level of practice. Our subjects (N=80) performed three computerized reaction-time and four tracking tasks both singly and concurrently. The performance of as many as 30 trials was obtained during 10 successive days of practice. The recorded performance is now being submitted to a series of factor analyses to compare the factor structure of single- and dual-task measures on both low and higher levels of practice. The obtained results will be presented and discussed.
ENG